The centrality of remembered moral and immoral actions in constructing personal identity. Issue 2 (7th February 2020) - Stanley, Matthew L.; Bedrov, Alisa; Cabeza, Roberto; De Brigard, Felipe
ABSTRACT: There is a widespread belief that morally good traits and qualities are particularly central to psychological constructions of personal identity. People have a strong tendency to believe that they truly are morally good. We suggest that autobiographical memories of past events involving moral actions may inform how we come to believe that we are morally good. In two studies, we investigated the role of remembered past events involving moral and immoral actions in constructing perceived personal identity. For morally right actions only, we found that remembered actions judged to be more morally right relative to less morally right were more central to personal identity (Study 1). We then found that remembered morally right actions were more central to personal identity than remembered morally wrong actions (Study 2). We discuss these findings in relation to recent research on morality and personal identity.